The first Brazilian troglobitic species of Cirolanidae (Isopoda, Cymothoida)—a potentially threatened species - Souza, Leila A.; Senna, André R.; Bento, Diego M.; Lima, Sergio M. Q.; Ferreira, Rodrigo L. (Zootaxa, 2025)
Brasilana spelaea gen. nov. et sp. nov. is described from caves from Rio Grande do Norte and Ceará states, northeast Brazil. Although this represents the first stygobiont species of Cirolanidae known for Brazil, it is already at risk of extinction considering the limestone industry, unregulated tourism, and subterranean water exploitation in most of the areas where it occurs. The new genus differs from its congeners by having a unique set of characters and exclusive traits, such as the geniculate antennular peduncle and the distal dorsal lobe in the posterior face of basis of pereopods 1–7. Although specimens of Brasilana spelaea gen. nov. et sp. nov. were collected from nine geographically distant caves, recent phylogeographic studies suggest that it belongs to a single species, likely dispersed through subterranean aquifers of the Jandaíra Formation. Additionally, the morphological and molecular phylogenetic analyses presented here provide robust support for the establishment of a new genus and species.